Market Leader. Business Law - Smith, Tricia (Harlow Pearson Education Limited, 2007)
Market Leader is an extensive new Business English course which brings the real world of international business into the classroom. Developed in association with the Financial Times, it offers the wideat and most flexible range of materials for learners and teachers alike.
Keywords: English Practice